THE THE EFFECT OF WORK ENVIRONMENT, MOTIVATION, AND CAREER DEVELOPMENT ON EMPLOYEE JOB SATISFACTION AT BALI MANDARA EYE HOSPITAL - I Nyoman Sukadana; Komang Krisna Heryanda; Made Ary Meitriana (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of work environment, motivation, and career development on employee job satisfaction at Bali Mandara Eye Hospital, Denpasar, Bali. A quantitative approach was employed using multiple linear regression analysis. The population consisted of 279 employees, with a sample of 164 respondents selected through Slovin's formula at a 5% error margin. Data were collected via structured questionnaires using a five-point Likert scale and analyzed using SPSS. The validity test showed all items had r-values above 0.1533 (r-table), and Cronbach's Alpha values exceeded 0.60, indicating reliable instruments. The results of the classical assumption tests confirmed that the data met the requirements of normality, multicollinearity, and homoscedasticity. The F-test showed a simultaneous significant effect (F = 83.514, p < 0.05), while individual t-tests revealed that work environment (t = 10.411, p < 0.001), motivation (t = 7.877, p < 0.001), and career development (t = 8.009, p < 0.001) each positively and significantly affected job satisfaction. The Adjusted R-Square of 0.603 indicates that 60.3% of job satisfaction variance is explained by the three variables. Work environment emerged as the most dominant predictor. These findings support Self-Determination Theory, Job Demands-Resources Theory, and Growth Mindset Theory, confirming the importance of an integrated approach in managing human resources in hospital settings. Keywords: Work Environment, Motivation, Career Development, Job Satisfaction, Hospital, Bali Mandara Eye Hospital